Harnessing the power of phylogenomics to disentangle the directionality and signatures of interkingdom host jumping in the parasitic fungal genus Tolypocladium. (2nd January 2018) - Quandt, C. Alisha; Patterson, Will; Spatafora, Joseph W.
ABSTRACT: Host specialization is common among parasitic fungi; however, there are examples when transitions in host specificity between disparately related hosts have occurred. Here, we examine the interkingdom host jump from insect pathogenicity and mycoparasitism in Tolypocladium . Previous phylogenetic inferences made using only a few genes and with poor support reconstructed an ancestral character state of insect pathogenesis, a transition to mycoparasitism, and reversions to insect pathogenesis. To further explore the directionality and genes underlying the transitions in host, we sequenced two additional species of Tolypocladium ( T. capitatum and T. paradoxum ) and used phylogenomics to compare two insect pathogens and two mycoparasites. Our whole-genome-scale analysis suggests that the diversification of Tolypocladium species happened relatively quickly and that the truffle parasites form a monophyletic, derived lineage within the genus that is the result of a single ecological transition or host jump from insects to fungi. A significant amount of gene tree/species tree discordance occurs within the data set, and we infer this to be the product of both an historical hybridization event and incomplete lineage sorting that was likely because of the rapid diversification of the clade. Furthermore, comparative genomic analyses revealed a set of genes that are exclusive to the mycoparasitic species. These potentially mycoparasitic gene clusters were characterized by a reduced proportion of secreted proteins when compared with entomopathogen-enriched genes and involved the reshaping of the fungal secretome in the ecological context of mycoparasitism.